Development of an agent-based indoor evacuation model for local fire risks analysis - Rui Feng Cao; Eric Wai Ming Lee; Wei Xie; Dong Li Gao; Qian Chen; Anthony Chun Yin Yuen; Guan Heng Yeoh; Richard-Kwok-Kit Yuen (Journal of Safety Science and Resilience, 2023)
Evidence suggests that in the event of a fire accident, a certain number of building occupants escape through smoke-filled environments. Consequently, evaluating the corresponding evacuation performance under such life-threatening conditions is important for advancing fire safety analyses. This study aimed to develop a fire-integrated evacuation model to consider the effects of spreading fire hazards (i.e., radiation, temperature, toxic gas, visibility) on evacuees in a room fire evacuation scenario. Furthermore, a novel quantitative approach was introduced to evaluate evacuees’ local fire risks and stress levels according to their egress paths. The escape characteristics at various stages of fire development were studied as well. The results demonstrate that evacuation performance varies considerably depending on the severity of evacuees’ confronted fire hazard conditions, which emphasizes the importance of minimizing the pre-evacuation time in fire evacuation emergencies.